Peer Assessment in Ecuadorian middle school EFL classrooms: effect on writing, engagement, and motivation: Evaluación entre pares en EFL clases en escuela de Ecuador: efecto en escritura, participación y motivación - Moncayo Triviño, Alejandro Henry; Guevara-Peñaranda, Ninfa Sofía (Boletín Científico Ideas y Voces, 2025)
The present study investigated the effect of Peer Assessment (PA) on performance, engagement, and motivation among middle school EFL writing students. This mixed-methods design study examined the rate of improvement in writing, measured changes in students’ levels of motivation and engagement, and explored teachers’ perceptions of the PA. The quantitative pre- and post-test data were collected from the control group (n=25) and experimental group (n=67). Moreover, the students of the experimental group filled out a questionnaire evaluating their PA activities as well. Additionally, qualitative data were obtained by interviewing teachers (n=5), who provided their views on the pros and cons of implementing PA in EFL instruction. Quantitative data was analyzed using descriptive statistics and a Paired t-test. The analysis of the qualitative data produced a thematic analysis, and coding was used to highlight repetition. Results demonstrated that the writing scores were significantly higher (M=8.76, p<.01). However, the means of Behavioral Engagement (M=11.11/15) and Emotional Engagement (M=10.83/15) indicated that students are willing to engage in the reviewing of peer assignments. Motivation (M=10.57) showed a possible difficulty of engagement or resistance toward applying PA in the classroom. During and after PA activities, teachers indicated high levels of motivation, confidence, and some improvement in writing skills.